Dispersion Characteristics of Complex Resistivity and Petroelectric Parameters of Deep Coal Seam in the Ordos Basin - DENG Ze; ZHAO Qun; FAN liyong; GE Xinmin; HUANG Daojun; SHI Lei; WANG Ziming; ZHANG Yonghao (Cejing jishu)
The complex pore structure, metamorphic degree and mineral components have a great impact on the electrical conductivity characteristics of deep coal seams, posing significant challenges to the evaluation of saturation based on electrical parameters. In order to clarify the electrical properties and core electrical parameters of deep coal seams, based on the samples of deep coal seam from the Benxi group in the Ordos basin, a series of supporting petrophysical experiments on complex resistivity under different test frequencies and different saturation states are carried out. A saturation correction model is established based on the difference between gas porosity and liquid porosity. Based on the difference between gas porosity and liquid porosity a saturation correction model is established. The relationship between the measured complex resistivity and saturation is fitted by power index to correct the complex resistivity of coal seam in complete water-bearing state, The frequency dispersion characteristics of complex resistivity of coal seam are analyzed, and the variation characteristics and physical mechanism of between core electrical parameters and water saturation, frequency are clarified. The results indicate that the complex resistivity, the resistivity index of coal seam is negatively correlated with water saturation and frequency, the saturation index is negatively correlated with the test frequency, while the cementation index is positively correlated with the test frequency. The calculation model of water saturation is established by the core electrical parameters corresponding to the frequency of 10 kHz, it is found that the calculated value is less than the measured value, and the average absolute error is 7.47%. For different resistivity logging methods and instruments, it is recommended to select appropriate core electrical data within the tested frequency band for saturation modeling. This study provides effective support for in-depth understanding of the electrical characteristics and saturation evaluation of deep coal seams.